Patient's perspective on an integrated knowledge translation tool in homecare occupational therapy. (30th September 2020) - Ruest, M; Léonard, G; Drolet, M J; Guay, M
Abstract: Background: Patient engagement and integrated knowledge translation (IKT) approaches involving end-users of knowledge are increasingly documented for their social benefits in the subsequent application of health innovations. Algo is an IKT-based algorithm conceived with occupational therapists (OTs; supervisors) and non-OTs (users) in Quebec's (Canada) public homecare services (HCS) to support skill mix for bathing equipment selection. However, the unknown patient experience related to Algo's utilization in HCS hinders the deployment of adjusted facilitation strategies for the beneficiaries. Methods: A multiple case study (case: a HCS minimally including an OT, a non-OT and a manager) was performed with semi-structured interviews and focus groups, based on the integrated-Promoting Action on Research Implementation in Health Services (i-PARIHS) model. For intra-case analysis, extracts related to patient's experience were analyzed thematically according to the i-PARIHS components (Innovation, Recipients and Context) by a patient collaborator who shares its recommendations. Results: Seventy-four (74) extracts from 5 cases referring to different trajectories of Algo's IKT process were analyzed by the patient collaborator and discussed through 5 interviews over 14 months. The following themes were identified: the promotion of Algo's relative advantage (Innovation) adjusted to the recipients' mandates, the consolidation of interprofessional collaboration between OTs, non-OTs, and managers (Recipients) and the development of their leadership abilities through the HCS instances (Context). Conclusions: Patient's recommendations on Algo's IKT process in public HCS will orientate next facilitation orientations for supporting its utilization with patients living occupational difficulties during hygiene care at home. The integration of these findings expands the epistemic perspectives considered for developing public health policies to positively impact on quality of patient care. Key messages: Patient's perspective should be involved in integrated knowledge translation studies in order to expand end-users' consideration in the development and application of knowledge. Patient's feedback on the knowledge translation process (i.e., knowledge, recipients and context characteristics) offers a holistic perspective of analysis for improving facilitation orientations.